HUBUNGAN KARAKTERISTIK LINGKUNGAN, DIMENSI CUSTOMER FOCUS DENGAN TOTAL QUALITY MANAGEMENT DAN KINERJA ORGANISASI (Studi pada Perusahaan Jasa di Kota Pekanbaru) - Yesi Mutia Basri (Program Studi Pendidikan Ekonomi Universitas Riau, 2012)
This study examines the relationship between environmental characteristic consistdynamism, complex and munificence with customer focus dimension in total qualitymanagement (TQM). Furthermore, it investigates relationship between customerfocus dimension in TQM and organization performance the empirical data for thisstudy was drawn from a survey of 58 middle/senior managers from sevices firms inRiau. The analysis was conducted using structural equation modeling (SEM) withPLS.The findings indicate that environmental characteristics have relation withcustomer focus and customer focus has relation and TQM.